Skip to main content

This notebook was created by Sergey Tomin (sergey.tomin@desy.de) and Martin Dohlus (DESY). May 2018.

8. Laser Heater

The OCELOT Charged Particle Beam Dynamics (CPBD) module includes various physics processes like CSR, SpaceCharge, Wake3D, BeamTransform. There are other "physics processes", which do not have anything in common with physics but use the same interface (or parent class "PhysProc") e.g. SaveBeam. Using this interface, one can implement own "physics process". In this tutorial we will show how to do it on the example of the laser heater.

We will start with the theory of the laser heater and then will show how to implement the heating process in the code.

Acknowledgment

We wish to thank Igor Zagorodnov for fruitful discussion.

Contents

  1. Theory of the laser heater 2. Electron motion in an undulator
    1. Gaussian beam
    2. Electric field amplitude of the laser beam
    3. Interaction of an electron with electromagnetic field
    4. Practical formulas and laser heater parameters
  2. Implementation of the LaserHeater class
  3. Simulation 8. Tracking without the laser heater effect 9. Tracking with the laser heater effect

Theory of the laser heater

Most of the expressions and the way to derive them were copied from the book [1]. Here we collect all parts together for educational purposes.

  1. Schmüser P., Dohlus M., Rossbach J., Behrens C. (2014) Undulator Radiation. In: Free-Electron Lasers in the Ultraviolet and X-Ray Regime. Springer Tracts in Modern Physics, vol 258. Springer, Cham

Electron motion in an undulator

First, we will consider electron motion in an undulator.

First order approximation

The equation of motion for an electron in the magnetic field is defined by:

γmev˙=ev×B\gamma m_e \dot{\mathbf{v}} = - e \mathbf{v} \times \mathbf{B}

which results into two coupled equations:

x¨=eγmeByz˙,z¨=eγmeByx˙\ddot{x} = \frac{e}{\gamma m_e} B_y \dot{z}, \qquad \ddot{z} = -\frac{e}{\gamma m_e} B_y \dot{x}

\qquad In the first order approximation vz=z˙v=βc=constv_z = \dot{z} \approx v = \beta c = const, vx<<vzv_x << v_z and z¨0\ddot{z} \approx 0 and taking into account the undulator magnetic field By=B0sin(kyz)B_y = -B_0\sin(k_y z) we get:

x(t)eB0γmeβcku2sin(kuβct),z(t)βctx(t) \approx \frac{e B_0}{\gamma m_e \beta c k_u^2}\sin(k_u \beta c t), \qquad z(t) \approx \beta c t

The electron travels on the sine-like trajectory

x(z)=Kβγkusin(kuz),x(z) = \frac {K} {\beta \gamma k_u}\sin(k_u z),

where K=eB0meckuK = \frac{eB_0}{m_e c k_u} and transverse velocity is

vx(t)=Kcγcos(kuβct)orvx(z)=Kcγcos(kuz)v_x(t) = \frac {K c}{\gamma} \cos(k_u \beta c t) \qquad or \qquad v_x(z) = \frac {K c}{\gamma} \cos(k_u z)

Second order approximation

The longitudinal component of the velocity is not constant in the undulator due to transverse motion:

vz=v2vx2=c2(11/γ2)vx2c(112γ2(1+γ2vx2/c2))v_z = \sqrt{v^2 - v_x^2} = \sqrt{c^2(1 - 1/\gamma^2) - v_x^2} \approx c\left(1 - \frac{1}{2\gamma^2} (1 + \gamma^2 v_x^2 / c^2) \right)

Inserting for vx=x˙(t)v_x = \dot{x}(t) and using the trigonometric identity cos2α=(1+cos2α)/2\cos^2 \alpha = (1 + \cos 2 \alpha)/2

vz(t)=(112γ2(1+K22))ccK24γ2cos(2ωut)v_z(t) = \left(1 - \frac{1}{2 \gamma^2}\left(1 + \frac{K^2}{2}\right) \right)c - \frac{c K^2}{4 \gamma^2}\cos(2 \omega_u t)

with ωu=βckucku\omega_u = \overline \beta c k_u \approx c k_u. The average longitudinal spead is:

vz=(112γ2(1+K22))cβc\boxed{\overline v_z = \left(1 - \frac{1}{2 \gamma^2}\left(1 + \frac{K^2}{2}\right) \right)c \equiv \overline \beta c}

The particle trajectory in the second order is described by:

x(t)=Kγkusin(ωut),z(t)=vztK28γ2kusin(2ωut)x(t) = \frac{K}{\gamma k_u} \sin(\omega_u t), \qquad \boxed{z(t) = \overline{v_z}t - \frac{K^2}{8\gamma^2 k_u}\sin(2\omega_u t)}

Gaussian beam

The light wave co-propagating with the relativistic electron beam is described by an electromagnetic wave:

E(x,y,z,t)=Re{E(x,y,z)ej(kzωt)}\mathbf{E}(x,y,z, t) = Re \{ E(x,y,z) e^{j (k z - \omega t)} \}

where

E(x,y,z)=E0e12x2σx2jz/k1jz/(kσx2)e12y2σy2jz/k1jz/(kσy2)E(x, y, z) = E_0 \frac{ e^{-\frac{1}{2} \frac{x^2}{\sigma_x^2 - j z/k} } } {\sqrt{1-j z/(k \sigma_x^2)}} \frac{ e^{-\frac{1}{2} \frac{y^2}{\sigma_y^2 - j z/k} } } {\sqrt{1-j z/(k \sigma_y^2)}}

Introducing Rayleigh length for xx and yy plane:

zRx=kσx2=2πσx2λ=πwx2λ,zRy=kσy2=2πσy2λ=πwy2λ\mathcal{z_{Rx}} = k \sigma_x^2 = \frac{2 \pi \sigma_x^2}{\lambda} = \frac {\pi w_x^2}{\lambda}, \qquad \mathcal{z_{Ry}} = k \sigma_y^2 = \frac{2 \pi \sigma_y^2}{\lambda} = \frac {\pi w_y^2}{\lambda}

we can write:

E(x,y,z)=E0ex2wx2j2z/k1jz/zRxey2wy2j2z/k1jz/zRyE(x, y, z) = E_0 \frac{ e^{-\frac{x^2}{w_x^2 - j 2 z/k} } } {\sqrt{1-j z/\mathcal{z_{Rx}}} } \frac{ e^{-\frac{y^2}{w_y^2 - j 2 z/k} } } {\sqrt{1-j z/\mathcal{z_{Ry}}}}

For a round beam and z=0z = 0:

E(x,y,0)=E0er2w2E(x,y,0) = E_0 e^{- \frac{r^2}{w^2}}

where ww is the waist size.

Electric field amplitude of the laser beam

Let's find the electric field amplitude E0E_0 of the laser beam.

Radiation power flow:

P(z,t)=SSdsP(z,t) = \int_{S_{\bot}} \langle \mathbf{S}\rangle ds

where ...\langle ... \rangle means averaging in time, S=E×H\mathbf{S} = \mathbf{E} \times \mathbf{H} - the Poynting vector.

For the plane wave:

S=12Z0E(x,y,z)2 \langle \mathbf{S}\rangle = \frac{1}{2 Z_0}|E(x,y,z)|^2

with Z0376.73Z_0 \approx 376.73 the impedance of free space. Now we consider the round beam at z=0z=0 with the waist radius ww

P(0)=12Z0E(x,y,0)2dxdy=E022Z0e2r2w22πrdr=πE02w24Z0\overline P(0) = \frac{1}{2 Z_0} \int |E(x,y,0)|^2 dx dy = \frac{E_0^2}{2 Z_0}\int e^{-2\frac{r^2}{w^2}}2\pi r dr = \frac{\pi E_0^2 w^2}{4 Z_0}

So, the electric field amplitude is

E0=4Z0P(0)πw2 E_0 = \sqrt{\frac{4 Z_0 \overline P(0) }{\pi w^2}}

Interaction of an electron with electromagnetic field

The energy transfer between the light wave and an electron is described by the equation:

W=eE(x,y,z,t)vdtW = e \int {\mathbf{E}(x,y,z,t) \cdot \mathbf{v} dt}

Averaging over time Ev\langle \mathbf{E} \mathbf{v}\rangle we can write an electron energy changes ΔE\Delta E after passing through an undulator with length LuL_u:

ΔE=eLuvzEv\Delta E = e \frac{L_u}{\overline{v_z}}\langle \mathbf{E} \mathbf{v}\rangle

Now consider only the term Ev\langle \mathbf{E} \mathbf{v}\rangle:

vx(t)Ex(x,y,z,t)=Re{E(x,y,z)ej(kz(t)ωt+ϕ0)Kcγcos(kuz(t))}=KcγRe{E(x,y,z)ej(kz(t)ωt)cos(kuz(t))}\begin{split} \langle v_x(t) E_x(x,y, & z, t)\rangle = \Big\langle Re \{ E(x,y,z) e^{j (k z(t) - \omega t + \phi_0)} \frac {K c}{\gamma} \cos(k_u z(t)) \} \Big\rangle = \\ &\frac {K c}{\gamma} Re \left\{ E(x,y,z)\Big\langle e^{j (k z(t) - \omega t )} \cos(k_u z(t)) \Big\rangle \right\} \end{split}

Please note, we chose ϕ0=0\phi_0 = 0 in exponential to simplify the notation, the phase accounts for the fact that the light wave will in general be phase-shifted against the sinusoidal trajectory of an arbitrary electron because the bunch is far longer than the light wavelength. This phase will be reintroduced in the last step.

Remembering from section [Electron motion in undulator](#Electron motion) z(t)=vztK28γ2kusin(2ωut)z(t) = \overline{v_z}t - \frac{K^2}{8\gamma^2 k_u}\sin(2\omega_u t).

ej(kz(t)ωt)cos(kuz(t))ej(kvztωtkK28γ2kusin(2ωut))cos(kuvzt)\Big\langle e^{j (k z(t) - \omega t)} \cos(k_u z(t)) \Big\rangle \approx \Big\langle e^{j \left( k \overline v_z t - \omega t - \frac{k K^2}{8\gamma^2 k_u}\sin(2\omega_u t)\right)} \cos(k_u \overline v_z t) \Big\rangle

Introducing new variable:

Y=kK28γ2ku=K24+2K2;Y = \frac{k K^2}{8\gamma^2 k_u} = \frac{K^2}{4 + 2 K^2};

and taking into account that:

cos(kuvzt)=ejkuvzt+ejkuvzt2\cos(k_u \overline v_z t) = \frac{e^{j k_u \overline v_z t } + e^{-j k_u \overline v_z t}}{2}

we can write

ej(kvztωtkK28γ2kusin(2kuvzt))cos(kuvzt)=ej(kvzω)tej(Ysin(2kuvzt))ejkuvzt+ejkuvzt2=ej((k+ku)vzω)tej(Ysin(2kuvzt))1+e2jkuvzt2\begin{split} \Big\langle e^{j \left( k \overline v_z t - \omega t - \frac{k K^2}{8\gamma^2 k_u}\sin(2 k_u \overline v_z t)\right)} & \cos(k_u \overline v_z t) \Big\rangle = \Big\langle e^{j(k \overline v_z - \omega) t} e^{j \left( - Y\sin(2 k_u \overline v_z t)\right)} \frac{e^{j k_u \overline v_z t } + e^{-j k_u \overline v_z t}}{2} \Big\rangle = \\ &\Big\langle e^{j((k + k_u)\overline v_z - \omega) t} e^{j \left( - Y\sin(2k_u \overline v_z t)\right)} \frac{1 + e^{-2 j k_u \overline v_z t }}{2} \Big\rangle \end{split}

Rewriting this expression using θ=2ωut=2vzkut\theta = 2\omega_u t = 2 \overline v_z k_u t, we obtain

ej((k+ku)vzω)tejθ+12ejYsinθ\Big \langle e^{j((k + k_u)\overline v_z - \omega) t} \frac{e^{-j\theta} + 1}{2} e^{-j Y \sin\theta}\Big\rangle

Discussion

The equation above I calculated in two ways (option 1 and option 2).

Option 1

The average velocity is

vz=(112γ2(1+K22))c\overline v_z = \left(1 - \frac{1}{2 \gamma^2}\left(1 + \frac{K^2}{2}\right) \right)c

If we consider resonance condition only for the first harmonic n=1n = 1:

λ=λu2γ2(1+K22)\lambda = \frac{\lambda_u}{2 \gamma^2}\left(1 + \frac{K^2}{2}\right)

then

vz=(1λλu)c\overline v_z = \left(1 - \frac{\lambda}{\lambda_u}\right) c

Inserting it into the argument of the fist exponential and neglecting a term of the second order of smallness we get:

(k+ku)vzω=(k+ku)(1λλu)ckc=0(k + k_u)\overline v_z - \omega = (k + k_u)\left(1 - \frac{\lambda}{\lambda_u}\right)c - k c = 0

and

ej((k+ku)vzω)tejθ+12ejYsinθ=ejθ+12ejYsinθ\Big \langle e^{j((k + k_u)\overline v_z - \omega) t} \frac{e^{-j\theta} + 1}{2} e^{-j Y \sin\theta}\Big\rangle = \Big \langle \frac{e^{-j\theta} + 1}{2} e^{-j Y \sin\theta}\Big\rangle

Taking into account the standard integral representation of the Bessel function for integer orders nn

Jn(x)=1π0πcos(nθxsinθ)dθ=12πππejnθ+jxsinθdθJ_n(x) = \frac{1}{\pi}\int_0^\pi \cos(n\theta - x \sin\theta)d\theta = \frac{1}{2\pi}\int_{-\pi}^\pi e^{-j n\theta + j x \sin\theta}d\theta

and the Bessel function property

Jn(x)=Jn(x)=(1)nJn(x)J_n(-x) = J_{-n}(x) = (-1)^n J_n(x)

we finaly get

ejθ+12ejYsinθ=J1(Y)+J0(Y)2=J0(Y)J1(Y)2\Big \langle \frac{e^{-j\theta} + 1}{2} e^{-j Y \sin\theta}\Big\rangle = \frac{J_{1}(-Y) + J_0(-Y)}{2} = \frac{J_{0}(Y) - J_1(Y)}{2}

Option 2

Expand the last exponential of the last equation from he previous section into a Fourier-Bessel series:

ejYsinθ=n=Jn(Y)ejnθe^{jY \sin \theta} = \sum_{n=-\infty}^{\infty} J_n(Y)e^{j n \theta} ej((k+ku)vzω)tejθ+12ejYsinθ=ej((k+ku)vzω)tejθ+12n=Jn(Y)ejnθ=ej((k+ku)vzω)t12{n=Jn(Y)ej(n1)θ+n=Jn(Y)ejnθ}\begin{split} \Big \langle e^{j((k + k_u) \overline v_z - \omega) t} & \frac{e^{-j\theta} + 1}{2} e^{-j Y \sin\theta}\Big\rangle = \Big \langle e^{j((k + k_u)\overline v_z - \omega) t} \frac{e^{-j\theta} + 1}{2} \sum_{n=-\infty}^{\infty} J_n(-Y)e^{j n \theta}\Big\rangle = \\ \Big \langle & e^{j((k + k_u)\overline v_z - \omega) t} \frac{1}{2}\Big\{\sum_{n'=-\infty}^{\infty} J_{n'}(-Y)e^{j (n' - 1) \theta} + \sum_{n=-\infty}^{\infty} J_n(-Y)e^{j n \theta}\Big\} \Big\rangle \end{split}

Making replacement n=n+1n' = n+1:

ej((k+ku)vzω)t12n={Jn+1(Y)+Jn(Y)}ejnθ\Big \langle e^{j((k + k_u)\overline v_z - \omega) t} \frac{1}{2}\sum_{n=-\infty}^{\infty} \Big\{J_{n+1}(-Y) + J_n(-Y)\Big\} e^{j n \theta} \Big\rangle

and remembering that θ=2vzkut\theta = 2 \overline v_z k_u t

12n={Jn+1(Y)+Jn(Y)}ej((k+(2n+1)ku)vzω)t\Big \langle \frac{1}{2}\sum_{n=-\infty}^{\infty} \Big\{J_{n+1}(-Y) + J_n(-Y)\Big\} e^{j((k + (2n + 1)k_u)\overline v_z - \omega) t} \Big\rangle

If we ensure fulfillment of the resonance condition only for the first harmonic as we did in the "Option 1" (in that case n=0n=0) the only one term of the sum will survive the only one term of the sum will survive. Indeed, for the n=0n=0 argument of the exponential will be constant but for other harmonic numbers it will oscillate and give in average 0. So our final expression:

ej((k+ku)vzω)tejθ+12ejYsinθ=J0(Y)J1(Y)2\boxed{\Big \langle e^{j((k + k_u)\overline v_z - \omega) t} \frac{e^{-j\theta} + 1}{2} e^{-j Y \sin\theta}\Big\rangle = \frac{J_{0}(Y) - J_1(Y)}{2}}

Continuation

Collect all together, we can write the term Ev\langle E v\rangle

Ev=KcγRe{E(x,y,z)}J0(Y)J1(Y)2\langle E v\rangle = \frac {K c}{\gamma} Re \left\{ E(x,y,z)\right\}\frac{J_{0}(Y) - J_{1}(Y)}{2}

Finally, remembering derivation of the electric field amplitude E0=4Z0P(0)πw2E_0 = \sqrt{\frac{4 Z_0 \overline P(0) }{\pi w^2}}, we can write expression for amplitude of energy modulation on axis (x=y=0x=y=0)

dE=eLuvzEv=eLuvzK~c2γRe{E(x,y,z)}=eLuK~2βγRe{E(0,0,0)}=eLuK~βγZ0P(0)πw2\begin{split} &d \mathscr E = e \frac{L_u}{\overline{v_z}}\langle \mathbf{E} \mathbf{v}\rangle = e \frac{L_u}{\overline{v_z}} \frac {\widetilde K c}{2\gamma} Re \left\{ E(x,y,z)\right\} = \\ & e \frac{L_u \widetilde K}{2 \overline{\beta} \gamma} Re \left\{ E(0,0,0)\right\} = e \frac{L_u \widetilde K}{\overline{\beta}\gamma} \sqrt{\frac{Z_0 \overline P(0) }{\pi w^2}} \end{split}

where K~=K(J0(Y)J1(Y))\widetilde K = K\cdot(J_{0}(Y) - J_{1}(Y))

With P0=4πZ0(mc2e)2=8.7GWP_0 = \frac{4\pi}{Z_0}\left( \frac{m c^2}{e}\right)^2 = 8.7\, GW and in eV units:

dE[eV]=2(mc2)2LuK~βEbeam[eV]wP(0)P0d \mathscr E [eV] = 2\frac{(mc^2)^2 L_u \widetilde K}{\overline{\beta} E_{beam}[eV] w} \sqrt{\frac{\overline P(0) }{P_0}}

Position and phase dependent energy modulation :

ΔE(x,y,ϕ)=dEex2+y24σl2cosϕ0\Delta E(x,y,\phi) = d \mathscr E e^{- \frac{x^2 + y^2}{4 \sigma_l^2}}\cos \phi_0

where ϕ0=2πλphzi\phi_0 = \frac{2\pi}{\lambda_{ph}}z_i is phase shift of the light wave against the sinusoidal trajectory of an arbitrary electron (with longitudinal coordinate ziz_i) what we chose 00 at the at the beginning of this journey.

Transverse particle distribution:

P(x,y)=12πσxσye(xx)22σx2(yy)22σy2P(x,y) = \frac{1}{2\pi \sigma_x \sigma_y} e^{- \frac{(x -\overline{x})^2}{2 \sigma_x^2} - \frac{(y -\overline{y})^2}{2 \sigma_y^2}}

RMS energy spread:

Erms=RdE=dϕ2πdxdy×P(x,y)(ΔE(x,y,ϕ))2\mathscr E_{rms} = R d \mathscr E = \sqrt{\int \frac{d\phi}{2\pi}dx dy\times P(x,y)(\Delta E(x,y,\phi))^2}

where RR - shape factor (particle-photon matching), for instance for round beam no offset R=12+2(σp/σI)2R = \frac{1}{\sqrt{2 + 2(\sigma_p/\sigma_I)^2}}

Practical formulas and the laser heater parameters

To simulate the laser heater process we need to calculate dEd \mathscr E and then using the expression for the [energy modulation](#practical formula) we can calculate the energy spread increasing. In that case, the shape factor will be automatically taking into account.

The laser power estimation.

Suppose we want to have energy spread Erms=RdE=12.5keV\mathscr E_{rms} = R d \mathscr E = 12.5\, keV. So we can estimate the laser beam power which is needed for that. We just need to invert the expression that we got before with minor modifications:

dE[eV]=2(mc2)2LuK~βEbeam[eV]wP(0)P0d \mathscr E [eV] = 2\frac{(mc^2)^2 L_u \widetilde K}{\overline{\beta} E_{beam}[eV] w} \sqrt{\frac{\overline P(0) }{P_0}}

The laser power is:

P(0)=(ErmsEβ2(mc2)2wRLuK~)2P0\overline P(0) = \left( \frac{\mathscr E_{rms} E \overline{\beta}}{2 (mc^2)^2} \frac{w }{R L_u \widetilde K }\right)^2 P_0

And finally, using expression for [position and phase dependent energy modulation](#practical formula), we can write the energy kick in the OCELOT coordinates for ii-particle passing dzdz of the laser heater undulator with the particle coordinates x,yx, y - transverse coordinates, {τ=cdt;  δ=ΔEp0c}\{\tau = cdt;\; \delta = \frac{\Delta E}{p_0 c}\} - longitudinal coordinates:

δi=δi+dEp0ce(xix)24σx2(yiy)24σy2cos(2πλphτi)dzLu\boxed{\delta_i = \delta_i + \frac{d \mathscr E}{p_0 c} e^{-\frac{(x_i - \overline x)^2}{4 \sigma_x^2}-\frac{(y_i - \overline y)^2}{4 \sigma_y^2}} \cos\left(\frac{2\pi}{\lambda_{ph}}\tau_i\right)\frac{dz}{L_u}}

with x,y\overline x, \overline y are laser beam misalignment, and σx,σy\sigma_x, \sigma_y are laser beam transversal sizes.

Playing with numbers

The laser power is:

P(0)=(Ermsγβ2(mc2)wRLuK~)2P0\overline P(0) = \left( \frac{\mathscr E_{rms} \gamma \overline{\beta}}{2 (mc^2)} \frac{w }{R L_u \widetilde K }\right)^2 P_0

where K~=K(J0(Y)J1(Y))\widetilde K = K\cdot(J_{0}(Y) - J_{1}(Y)), Y=K24+2K2Y = \frac{K^2}{4 + 2 K^2}

K=2λλu2γ22K = \sqrt{2\frac{\lambda}{\lambda_u}2\gamma^2 - 2}

γ>>1\gamma>> 1

K=2γλλuK = 2 \gamma \sqrt{\frac{\lambda}{\lambda_u}}

Substitute

P(0)=(Ermsγβ2(mc2)wRLu2γλλu(J0(Y)J1(Y)))2P0\overline P(0) = \left( \frac{\mathscr E_{rms} \gamma \overline{\beta}}{2 (mc^2)} \frac{w }{R L_u 2 \gamma \sqrt{\frac{\lambda}{\lambda_u}}\cdot(J_{0}(Y) - J_{1}(Y)) }\right)^2 P_0 P(0)=λuλ(Ermsβ4(mc2)wRLu(J0(Y)J1(Y)))2P0\overline P(0) = \frac{\lambda_u}{\lambda} \left( \frac{\mathscr E_{rms} \overline{\beta}}{4 (mc^2)} \frac{w }{R L_u (J_{0}(Y) - J_{1}(Y)) }\right)^2 P_0

Assuming that optimal modulator length is equal Lu=2zR=2πw2λL_u = 2 \cdot \mathcal{z_{R}} = 2 \frac{\pi w^2}{\lambda}

P(0)=λuλ1(Ermsβ8π(mc2)1Rw(J0(Y)J1(Y)))2P0\overline P(0) = \frac{\lambda_u \lambda}{1} \left( \frac{\mathscr E_{rms} \overline{\beta}}{8 \pi (mc^2)} \frac{1 }{R w (J_{0}(Y) - J_{1}(Y)) }\right)^2 P_0

the waist size

w=2Ax+2σxw = 2 A_x + 2 \sigma_{x}

amplitude of wiggling

Ax=Kγku=Kλu2πγ=λλuπA_x = \frac{K}{\gamma k_u} = \frac{K \lambda_u}{2 \pi \gamma } = \frac{\sqrt{\lambda \lambda_u}}{ \pi }
import numpy as np
from scipy.special import jv
from ocelot import *



def K2field(K, lu = 0.04):
field = K*m_e_eV*2.*pi/(lu*speed_of_light)
return field


# RMS energy modulation
Erms = 4e6 # eV
# electron beam energy
Eb = 2.4e9 # eV
#Eb = 17.5e9 # eV
# wavelength
l_ph = 800e-9

mc2 = 0.511e6
gamma = Eb/mc2


print("gamma = ", gamma)
# undulator period length
lperiod = 0.2 # m
print("lperiod = ", lperiod)
K = 2*gamma * np.sqrt(l_ph/lperiod)

print("K estimated = ", K)
print("B estimated = ", K2field(K, lu=lperiod))
ku = 2*np.pi/lperiod
# beam size
sigma_x = 50e-6 # m
# Undulator length


# Undulator parameter
#Ku = 18.8
Ku = K
# Impedance of free space
Z0 = 376.73 # Ohm
# shape factor - ideal matching
R = 0.5
P0 = 8.7e9 # GW
Y = Ku**2/(4+2*Ku**2)
# amplitude of beam oscilation in modulator
Ax = Ku/(gamma * ku)
print("amplitude of oscilation", Ax*1e6, " um")
# the waist radius
w = 2*sigma_x + 2 * Ax
print("waist = ", w * 1e6, " um")

# Rayleigh length
Zr = np.pi*w**2/l_ph
Lu = 2 * Zr# m
print("Zr = ", Zr, " m")

# Laser power to obtain Erms energy spread with shape factor R
P = (Erms*Eb*w/(2*mc2**2*R*Lu*Ku*(-jv(1,Y) + jv(0, Y))))**2*P0
print("Laser power =", P*1e-9, "GW")
    initializing ocelot...
gamma = 4696.673189823875
lperiod = 0.2
K estimated = 18.7866927592955
B estimated = 1.0060033803412982
amplitude of oscilation 127.32395447351627 um
waist = 354.64790894703253 um
Zr = 0.49391781711690497 m
Laser power = 8.810302238315355 GW

Parameters of the European XFEL LH:

import numpy as np
from scipy.special import jv

# RMS energy spread
Erms = 20e3 # eV
# electron beam energy
Eb = 130e6 # eV
mc2 = 0.511e6
# undulator period length
lperiod = 0.074 # m
# beam size
sigma_I = 300e-6 # m
# Undulator length
Lu = 0.666 # m
# Undulator parameter
Ku = 1.294
# Impedance of free space
Z0 = 376.73 # Ohm
# shape factor - ideal matching
R = 0.5
P0 = 8.7e9 # GW
Y = Ku**2/(4+2*Ku**2)
# the waist radius
w = 2*sigma_I

# Laser power to obtain Erms energy spread with shape factor R
P = (Erms*Eb*w/(2*mc2**2*R*Lu*Ku*(-jv(1,Y) + jv(0, Y))))**2*P0
print("Laser power =", P, "W")
    Laser power = 547479.6570391625 W

Implementation of the LaserHeater class

To create class LaserHeater we use parent class PhysProc that includes two standard methods: prepare(self, MagneticLattice) and apply(self, ParticleArray, dz).

To implement the energy kick from the laser heater we just need redefine method apply(self, ParticleArray, dz)

But first, we import main OCELOT modules and functions and class PhysProc will be imported as well.

# the output of plotting commands is displayed inline within frontends, 
# directly below the code cell that produced it
%matplotlib inline

# this python library provides generic shallow (copy)
# and deep copy (deepcopy) operations
from copy import deepcopy

# import from Ocelot graphical modules
from ocelot.gui.accelerator import *

# import injector lattice
from injector_lattice import *
# import from Ocelot main modules and functions
# including parent class PhysProc
from ocelot import *

class LaserHeater(PhysProc):
def __init__(self, step=1):
PhysProc.__init__(self, step=step)
# amplitude of energy modulation on axis
self.dE = 12500e-9 # GeV
self.Ku = 1.294 # undulator parameter
self.Lu = 0.8 # [m] - undulator length
self.lperiod = 0.074 # [m] - undulator period length
self.sigma_l = 300e-6 # [m]
self.sigma_x = self.sigma_l
self.sigma_y = self.sigma_l
self.x_mean = 0
self.y_mean = 0

def apply(self, p_array, dz):
gamma = p_array.E/m_e_GeV
lbda_ph = self.lperiod/(2*gamma**2)*(1+self.Ku**2/2)
k_ph = 2*np.pi/lbda_ph
pc = np.sqrt(p_array.E**2 - m_e_GeV**2)

A = self.dE/(pc)*dz/self.Lu
dx = p_array.x()[:] - self.x_mean
dy = p_array.y()[:] - self.y_mean
p_array.p()[:] += A*np.cos(k_ph*p_array.tau()[:])*np.exp(
-0.25*dx**2/self.sigma_x**2
-0.25*dy**2/self.sigma_y**2)

Simulation

As the first step, we will import injector lattice and calculate linear optics. All steps were explained in the Tutorial N2 "Tracking".

lat = MagneticLattice(cell, stop=EOD_51_I1)

# initialization of Twiss object
tws0 = Twiss()
# defining initial twiss parameters
tws0.beta_x = 29.171
tws0.beta_y = 29.171
tws0.alpha_x = 10.955
tws0.alpha_y = 10.955
# defining initial electron energy in GeV
tws0.E = 0.005
# calculate optical functions with initial twiss parameters
tws = twiss(lat, tws0, nPoints=None)
# ploting twiss paramentrs.
plot_opt_func(lat, tws, top_plot=["Dx"], fig_name="i1", legend=False)
plt.show()

png

Laser heater undulator is shown as a pink block, blue blocks are dipoles of LH chicane

Tracking without laser heater effect

p_array_init = load_particle_array("sc_beam.npz")
p_array = deepcopy(p_array_init)

navi = Navigator(lat)
navi.unit_step = 0.1
tws_track, p_array = track(lat, p_array, navi)
    z = 28.044004999924 / 28.04400499992401. Applied: d: 
show_e_beam(p_array, figsize=(8,6))

png

Tracking with Laser heater effect

p_array = deepcopy(p_array_init)

navi = Navigator(lat)
navi.unit_step = 0.1
lh = LaserHeater()
lh.sigma_l = 0.0
navi.add_physics_proc(lh, und_start, und_stop)

tws_track, p_array = track(lat, p_array, navi)
show_e_beam(p_array, figsize=(8,6))
    z = 28.044004999924 / 28.04400499992401. Applied: d: erHeaterter

png